2017
DOI: 10.1007/s00103-017-2547-4
|View full text |Cite
|
Sign up to set email alerts
|

Allergie – eine Umwelterkrankung!

Abstract: The increase in allergies is a phenomenon that is being observed in all fast-developing countries. For a long time, science has taken as a starting point that solely a genetic predisposition is a precondition for the development of an allergy. Today, knowledge of environmental factors that can alter genes or the transcription of genes in the cells, has improved. Epidemiological studies have meanwhile identified several environmental factors that have a protective or supporting effect on allergy development. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…Nowadays, allergies have become an important public health problem in the urban environment of industrialised countries. This sickness is considered a global pandemic with a great impact on the worldwide economy [6,7]. In general, a higher prevalence of cases of sensitization related to pollen was detected in urban environments compared to rural areas [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, allergies have become an important public health problem in the urban environment of industrialised countries. This sickness is considered a global pandemic with a great impact on the worldwide economy [6,7]. In general, a higher prevalence of cases of sensitization related to pollen was detected in urban environments compared to rural areas [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a complex, multifactorial disease, dependent on an interaction of genetic predisposition and environmental factors 4 . Based on western lifestyle and increased urban living, the obesity pandemic co‐occurs with a steady rise in allergic diseases 5‐7 . Today, approximately 30–40% of the population suffers from one or more allergic condition and the prevalence is increasing dramatically in developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…4 Based on western lifestyle and increased urban living, the obesity pandemic co-occurs with a steady rise in allergic diseases. [5][6][7] Today, approximately 30-40% of the population suffers from one or more allergic condition and the prevalence is increasing dramatically in developed and developing countries. Importantly, previous studies identified the metabolic syndrome as a major risk factor for the development of asthma.…”
Section: Introductionmentioning
confidence: 99%